Physical fitness of first-year students: the role of living conditions - Shilko V.G. ,; Guseva N.L. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to track the changes in the physical fitness and health indicators of students from the start of the pandemic to the present day. Methods and structure of the study. A comparative analysis of indicators of physical fitness and health status of first-year students from 23 faculties and institutes of National Research TSU was carried out in the pre-pandemic (2019), post-pandemic (2022) periods of life and two years after the end of the pandemic (2023). Results and conclusions. A comparative examination of the physical fitness of first-year students across three distinct academic years, focusing on the quantity and intensity of physical activity, revealed a clear and statistically significant (p<0.05) decline in the development of physical attributes (for both males and females) in the 2022-2023 academic year compared to the 2019 academic year. This decline suggests a lack of sufficient physical exercise in the form of physical activities. The authors suggest that one of the primary objectives of physical education should be to foster students' motivation to engage in more physical activity. Introduction. The period 2019-2023 was marked by major changes in the format of educational activities associated with the pandemic and its end - this is the introduction, along with traditional, distance and blended forms of learning. These changes significantly affected the level of physical activity of university students, and also affected their psychophysical condition. In this regard, it seems relevant to track changes in the indicators of physical fitness and functional state of student youth during the pandemic and post-pandemic periods. A comparative analysis allows us to identify effective means of physical activity in improving the health of students.